Advances in the treatment of relapsed/refractory marginal zone lymphoma - Wang, Haotian; Wan, Xin; Zhang, Ying; Guo, Jing; Bai, Ou (Frontiers in Oncology, 2024)
Marginal zone lymphoma (MZL) is the second most common subtype of inert B-cell non-Hodgkin's lymphoma, accounting for 5-15% of non-Hodgkin's lymphoma cases. Patients with MZL have a long survival period, with a median survival of >10 years, and patients treated with a combination of anti-CD20 monoclonal antibody can achieve an overall effective rate of 81%. However, 20% of patients with MZL show relapse or experience disease progression within 2 years, with a median survival of only 3-5 years. Currently, the treatment options for patients with relapsed/refractory (R/R) MZL are limited, underscoring the pressing need for novel therapeutic drugs. The advent of novel anti-CD20 monoclonal antibodies, small molecule kinase inhibitors, immunomodulators, and other therapeutic strategies has ushered in a new era in the treatment of R/R MZL. Our objective is to summarize the existing treatment strategies, including immunotherapy and the emergent targeted therapies, and to evaluate their effectiveness and safety in the management of R/R MZL. By doing so, we aim to provide a clear understanding of the therapeutic landscape for R/R MZL, and to guide future research directions toward improving the prognosis and quality of life for patients afflicted with this challenging disease.